2014
DOI: 10.1111/cns.12357
|View full text |Cite
|
Sign up to set email alerts
|

Primaquine Treatment Suppresses Experimental Autoimmune Encephalomyelitis Severity

Abstract: Experimental autoimmune encephalomyelitis (EAE) is a T cell-dependent disease that mimics human multiple sclerosis (MS). The inflammation in the central nervous system (CNS) is a hallmark in these autoimmune inflammatory conditions [1]. Therefore, the development of new drugs that target the infiltration of inflammatory cells to the CNS is desired [2,3]. In this context, accumulating evidences place antimalarial drugs as immunomodulatory agents. For instance, administration of chloroquine, a weak base that has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It was previously shown that dihydroartemisinin reduced the clinical course of EAE through the inhibition of the mammalian target of rampamycin (mTOR) signaling pathway and increase in Treg numbers [ 12 ]. Likewise, we showed previously that, chloroquine, and its analogue primaquine, is able to reduce the severity of Experimental Autoimmune Encephalomyelitis through the elicitation of regulatory T cells [ 11 , 30 ]. Thus, drugs that rise Treg cells numbers are desired to control autoimmunity [ 22 , 31 ].…”
Section: Discussionmentioning
confidence: 86%
“…It was previously shown that dihydroartemisinin reduced the clinical course of EAE through the inhibition of the mammalian target of rampamycin (mTOR) signaling pathway and increase in Treg numbers [ 12 ]. Likewise, we showed previously that, chloroquine, and its analogue primaquine, is able to reduce the severity of Experimental Autoimmune Encephalomyelitis through the elicitation of regulatory T cells [ 11 , 30 ]. Thus, drugs that rise Treg cells numbers are desired to control autoimmunity [ 22 , 31 ].…”
Section: Discussionmentioning
confidence: 86%
“…Primaquine is an antimicrobial used for the treatment of malaria and pneumocystis jiroveci. While our finding that primaquine may protect against renal IRI appears counterintuitive, as this drug is known to induce oxidative stress, it remains possible that its beneficial effects may derive from its anti-inflammatory actions [84]. Pimozide is a diphenylbutylpiperidine that can be used to treat schizophrenia, Tourette's syndrome, and recurrent tic [85].…”
Section: Discussionmentioning
confidence: 89%
“…Many drugs that were used in the treatment of infections have discovered new uses in the amelioration of inflammation, which is the case of chloroquine, primaquine, dihydroxyartemisinin, and artesunate, among others [19][20][21][22][23][24]. Artesunate (Art), a semi-synthetic sesquiterpene derived from Artemisia annua L., has originally been used in the treatment of malaria [25,26].…”
Section: Introductionmentioning
confidence: 99%